TREATING BONE CANCER AT THE EARLY STAGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, July 2016 Cancer is a dreadful disease which might cause death, but can be treated in several ways such as chemotherapy, radiotherapy or surgery and taking medications.